DEVELOPING NEUROSURGERY IN UZBEKISTAN, FOLLOWING THE EXAMPLE OF DEVELOPED COUNTRIES - Xursanjonov Jasurbek Ma’mirjon o’g’li; Abduqayumova Sevinch Muhiddin qizi; Qurbonova Malohat (Web of Journals Publishing, 2025)
The development of neurosurgery in Uzbekistan represents a crucial step in modernizing the national healthcare system and improving the quality of specialized medical services. This article explores the current state of neurosurgery in Uzbekistan, identifies key challenges faced by the sector, and analyzes successful strategies implemented by developed countries such as the United States, Germany, and Japan. The study emphasizes the importance of adopting international best practices, including advanced training of neurosurgeons, investments in high-precision medical technologies, and the integration of telemedicine. The article also highlights the role of institutional reforms, international cooperation, and public-private partnerships in accelerating progress. Based on comparative analysis, practical recommendations are proposed to enhance neurosurgical capacity in Uzbekistan and align it with global standards.
Keywords: Neurosurgery, Uzbekistan, medical development, healthcare reform, developed countries, medical technologies, international collaboration, telemedicine, professional training, healthcare modernization.